PERENCANAAN PENGGANTIAN JEMBATAN TINJOMOYO KOTA SEMARANG - Rani Wijayanti; Wisnu Dwi Sampurno; Moga Narayudha; Indrastono Dwi Atmanto (Jurnal Karya Teknik Sipil, 2013)
Along with growth of density of traffic getting through joint streets of Ngadirojo Biting so government of Province Central Java of has a plan to  innovate Bridge of Mider III . This Matter because of the Bridge have passed plan and also Wonogiri is area which is expanding and the position of strategic that is connecting Sub-Province of Wonogiri Central Java with Sub-Province of Ponorogo Java East. Replacment of Mider III Bridge to be build  this is prestressed-concrete Bridge with length 50 meters. This bridge consist of two unfolding limited by one pillar and two abutment. The width of bridge is  9,7  m that  consists of 2 traffic lanes, 3,5 m width of each lane and there are pavement 1  m width in the right and left side of the bridge. For upper structure, there are reinforced concrete for floor bridge, and the girders uses 10 prestreesed concrete type I height (H) 1600 mm. For under structure consists of reinforced concrete abutment with contrafort, and for pillar, it is made from reinforced concrete with rectangle shape 3 m x 3 m, and for foundations its used The Foundation using the  sinks foundation with diameter 3,5 m  for abutment and 5 m  for pillar , the depth of the  sinks  foundation for abutment is 5 m  and the depth of the  sinks  foundation for pillar  is 7 m. On the design of this bridge,Mider III is planned also connection way between bridge and ring road way which is called oprit are also designed. Each way has length 125 m and it is same on Wonogiri destination and Ponorogo  destination. This connection way uses flexible pavement with laston thick 100 mm, base course foundation with class A aggregate thick  200 mm, upper course foundation with sirtu class B thick  400 mm. Based on the bill of quantity the design of Tambakboyo bridge needs Rp 5.063.827.000,00 (Five Billion Sixty Three Million Eight Hundreds twenty seven Thousand rupiah ) and PPN 10 % Rp 506.382.700,00 (Five Hundreds Six Million Three Hundred eighty two Thousands Seven Hundred Rupiah). While this project can be finished on 34 weeks.